The Influence of Financial Literacy, M-Banking Services on Saving Behavior Moderated by Gender and Self-Control - Hasna Nur Faramida; Muhammad Sabandi; Dini Octoria (Universitas Negeri Semarang, 2023)
This research aims to determine the influence of financial literacy and mobile banking services on the saving behavior of UNS students and to find out whether gender and self-control can moderate financial literacy and mobile banking services on the saving behavior of UNS students. This study uses a type of quantitative research with a population of UNS students. The determined sample of 144 samples was taken using a non probably sampling technique. The data collection technique uses a five-point Likert scale of 1-5 points distributed via Google Forms. Test the validity of the instrument using Confirmatory Factor Analysis (CFA) and test the reliability using Cronbach Alpha (a). All data is processed using SPSS 25 software. The results of the study prove that: (1) there is a significant and positive effect of financial literacy on saving behavior of UNS students; (2) there is a significant and positive effect of mobile banking services on saving behavior of UNS students; (3) gender can moderate financial literacy and mobile banking services on saving behavior UNS students; and (4) self-control can moderate financial literacy and mobile banking services on saving behavior of UNS students.